Understanding the use of vocabulary learning strategies among Malaysia ESL tertiary learners - Hossenini, Atefeh (2010)
This study investigates eight ESL students studying Teaching English as a Second Language in Universiti Putra Malaysia. This investigation attempts to understand the use of a variety vocabulary learning strategies employed by participants as well as the role of both formal and informal language learning environments on learners’ choice of vocabulary learning strategies. This study describes how school and home environments as well as how mediating agents interfere in acquiring vocabulary learning strategies of ESL students or support them. This research adopts the qualitative method. The researcher gathered data through in depth interviews and used open coding to code the data as well as constant comparative methods to analyze the data. The findings of the research show that participants learned new English words by using vocabulary learning strategies such as guessing from the textual context , using monolingual dictionaries,practicing newly learned vocabulary in conversations, using English language media and using social strategies. The findings suggest that the teachers’ teaching methods, the level of encouragement they received, peers’ negative and positive behaviors, classroom’s activity and textbooks were significant factors that generally effected the learners’ choice of vocabulary learning strategies in school. In the home environment, findings illustrate how parents’ encouragements and support as well as their educational level have an impact on learners’ vocabulary learning strategies. Additionally, the study found that learner’s beliefs have certain influence on both formal and informal ways of learning English vocabularies. The results of this study suggest that more vocabulary teaching with communicative approach focusing on factors such as learners’ language learning experiences, home environment and peer groups are needed in handling the Malaysians ESL learners as far as vocabulary learning’s concerned.